Flayed corpse and other stories - Simmons, Josh 1978- (Fantagraphics Books, 2018)
"Brutal, deeply unsettling, and often hilarious stories from a master of modern horror comics. Flayed Corpse and Other Stories contains more than two dozen of examples of Simmons's deft voice and vision. The individual stories in Flayed Corpse stand on their own as minimasterpieces of skin-crawling terror, but collectively complement each other in a way that only heightens the anxiety and dread pouring from page to page. Flayed Corpse also collects several collaborations between Simmons and other cartoonists, including James Romberger, Anders Nilsen, Tara Booth, Eroyn Franklin, Tom Van Deusen, and Eric Reynolds, amongst others"--Amazon
"Rated Hard R/Ultra-Depressoid"--Back cover
Keywords: Serial murderers -- Comic books, strips, etc; Self-mutilation -- Comic books, strips, etc; Monsters -- Comic books, strips, etc; Horror comic books, strips, etc -- United States; Comic books, strips, etc -- United States; Selbstbeschädigung; Horrorerzählung; Mord; Ungeheuer; Rückfalltäter; Comic